Characterization of fluorescent Pseudomonas with crop specific plant growth promoting responses on wheat and cow pea - AMROTIN TETA, ANIL S. KOTASTHANE; TOSHY AGARWAL, VANDANA SHUKLA*, NITIN KUMAR TORRAY (Indian Phytopathology, 2016)
Siderophores producing and Cynogenic (HCN producers) fluorescent pseudomonads exerted strong inhibitory against Sclerotium rolfsii. Descriptive method was used with the analysis of IAA production, gelatine hydrolysis, starch hydrolysis, lipolytic activity, casein hydrolysis, carbohydrate fermentation, litmus milk reaction, Arginine dihydrolase test, nitrate reduction, egg yolk test, phosphate solubilisation, siderophore production and antibiotic sensitivity. Plant growth promoting response of wheat, and cow pea was observed following seed bacterization with fluorescent Pseudomonas (expressing different levels siderophore) isolates. Fluorescent pseudomonas isolates P66 (Wheat (Triticum aestivum) and P229 (Cowpea (Vigna unguiculata var. AS-77) induced crop specific growth promoting response.